Relationship between oxidative stress biomarkers and micronuclei scoring as a biomarker for DNA damage in Egyptian nicotine-dependent smokers: A cross-sectional study - Asmaa Mahmoud Mohammed; Dalia Farouk; Adel F. Hashish (Journal of the Arab Society for Medical Research)
Background/aim About one-fifth of cancer deaths are caused by tobacco smoking. Nicotine-related DNA damage is thought to be the result of oxidative stress, whereas DNA damage can be represented in the form of binucleated micronuclei (BMNi). The aim of this study is to determine the relationship between oxidative stress biomarkers and micronuclei scoring in nicotine-dependent smokers. Subjects and methods The present study enrolled 112 Egyptian male participants, of which 45 nicotine-dependent smokers matched with 67 nonsmokers. All participants have been clinically evaluated and investigated for oxidative stress biomarkers, cytogenetic analysis of BMNi, and urinary cotinine creatinine ratio concentration. Results The smokers showed significantly higher mean values of the serum malondialdehayde concentration (P<0.05), and lower mean values of both reduced glutathione concentration and the serum total antioxidant capacity (P<0.05) in comparison to the nonsmokers. Moreover, the smokers showed significantly higher mean values of binucleated micronuclei score (P<0.05) than the nonsmokers. The linear regression model predicted that each increase in the serum malondialdehyde by 1 nmol/ml could increase the BMNi score by 2.7. On the other side, it is predicted that each decrease in the age of starting smoking by a year could be associated with a decrease in the plasma level of reduced glutathione by 0.5 mg/dl. Conclusion Serum level of MDA is a reliable tool to predict the binucleated micronuclei score in smokers. It is suggested that smoking at earlier ages worsens the natural antioxidant defense system. Smoking cessation and the use of supplementary antioxidants by smokers may regress the oxidative stress-induced DNA-damage.